Home networking - Thiruvathukal, G.K. (Computing in science & engineering, 2006)
Although most of the ideas behind networking are relatively straightforward, several interesting technical and business decisions must be made as an ongoing part of the process. In this first installment of what I hope turns into a discussion about more advanced applications, the focus is on revealing the secrets in a typical home router/switch. (Here, a router has both switching and routing functions).